2020
DOI: 10.1021/jacs.9b13768
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Synthesis and Characterization of Tris- and Tetra-Prato Adducts of M3N@C80 (M = Y, Gd)

Abstract: The tris- and tetra-adducts of M3N@I h -C80 metallofullerenes were synthesized and characterized for the first time. The 1,3-dipolar cycloaddition (Prato reaction) of Y3N@I h-C80 and Gd3N@I h-C80 with an excess of N-ethylglycine and formaldehyde provided tris- and tetra-fulleropyrrolidine adducts in a regioselective manner. Purification by HPLC and analyses of the isolated peaks by NMR, MS, and vis-NIR spectra revealed that the major products were four tris- and one tetra-isomers for both Y3N@I h-C80 and Gd3N@… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
(154 reference statements)
0
9
0
Order By: Relevance
“…[1][2][3][4] Exohedral functionalization of EMFs has shown its effectiveness to broaden their applications by generation a variety of useful derivatives. During the last decades, many synthetic methods have been applied to modify EMFs, among which cycloadditions, such as the BingelHirsch reaction, 5,6 [2+2] benzyne addition, 7, 8 1,3dipolar reaction, [9][10][11][12] DielsAlder reaction, 13 carbene addition 14 and so on, 5,15,16 have been widely utilized. Results show that the chemical properties of EMFs are much different from those of empty fullerenes, resulting in a fact that some chemical reactions which are effective to C 60 do not work on EMFs.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Exohedral functionalization of EMFs has shown its effectiveness to broaden their applications by generation a variety of useful derivatives. During the last decades, many synthetic methods have been applied to modify EMFs, among which cycloadditions, such as the BingelHirsch reaction, 5,6 [2+2] benzyne addition, 7, 8 1,3dipolar reaction, [9][10][11][12] DielsAlder reaction, 13 carbene addition 14 and so on, 5,15,16 have been widely utilized. Results show that the chemical properties of EMFs are much different from those of empty fullerenes, resulting in a fact that some chemical reactions which are effective to C 60 do not work on EMFs.…”
Section: Introductionmentioning
confidence: 99%
“…33 In functionalized NCFs, fully ordered clusters were mostly achieved via direct and strong interactions between the functional group and the cage (e.g., multiadditions or formal charge on the ligand and cage, etc.). 16b 21c 24 34 Our work demonstrated that weak intermolecular interactions between the organic ligands and the NCF cage can also restrict the cluster motion in the solid state of synthetically straightforward monoadducts, which provides a new direction of materials design for magnetic and quantum applications.…”
Section: Isocyanide-induced Fullerene/emf Reactions With Substituted ...mentioning
confidence: 88%
“…In particular, in 2020, Semivrazhskaya et al synthesized regioselective tris-and tetra-Prato adducts of M 3 N@C 80 (M = Y, Gd) to design new nitride EMF-based materials. 35 Coincidentally, the group of Aroua systematically investigated the Prato reaction of M 3 N@I h -C 80 (M = Sc, Lu, Y, Gd) with reversible isomerization. 36 At present, paramagnetic endohedral EMFs with unpaired electrons have drawn more attention owing to their extraordinary configurations and unique spin properties, making them promising candidates for quantum information processing, molecular machines, [37][38][39][40] etc.…”
Section: Introductionmentioning
confidence: 99%